Arginine Vasopressin and Arginine Vasopressin Receptor 1b Involved in Electroacupuncture‐Attenuated Hypothalamic‐Pituitary‐Adrenal Axis Hyperactivity in Hepatectomy Rats. Issue 5 (16th November 2015) - Zhu, Jing; Chen, Zhejun; Zhu, LiTing; Meng, ZeHui; Wu, GenCheng; Tian, ZhanZhuang
Abstract : Objective: The study aims to know the effect of electroacupuncture (EA) in maintenance of the homeostasis of the neuroendocrine system in hepatectomy rats and the involvement of arginine vasopressin (AVP) signaling in hypothalamus after EA was observed. Materials and Methods: Rats were randomly assigned to four groups, including the intact group, model group, sham‐EA group, and EA group. EA was given during the perioperative period at the Zusanli (ST36) and Sanyinjiao (SP6) points after hepatectomy. The serum adrenocorticotropic hormone (ACTH) and corticosterone (CORT) levels were detected via radioimmunoassay. The expression of AVP, arginine vasopressin receptor 1a (AVPR1a), arginine vasopressin receptor 1b (AVPR1b), and glucocorticoid receptor (GR) was detected by Western blot after surgery. Results: Compared with the intact group, the ACTH and CORT levels in the serum of model group were increased, whereas the ACTH and CORT levels were decreased in the EA group compared with the model group. Moreover, AVP and AVPR1b protein levels in the pituitary gland were increased in the model group and decreased in the EA group. Further, a distinct increase in the AVP and AVPR1a protein levels was observed in the model group, whereas they were significantly decreased in the EA group. Blockade of AVPR1b by nelivaptan reduced the increase of ACTH and CORT. D [Leu 4, Lys 8 ] vasopressin can inhibit the effect of EA in rectification of the hyperactivity of the hypothalamic‐pituitary‐adrenal (HPA) axis. Conclusions: EA application at ST36 and SP6 can ameliorate the hyperactivity of the HPA axis via AVP signaling during the perioperative period.